Pembentukan Majelis Kehormatan Mahkamah Konstitusi Sebagai Pengawas Etik Hakim Konstitusi - Andika Abay, Rahmad (WELFARE STATE Jurnal Hukum, 2025)
The establishment of the Honor Council of the Constitutional Court as the Ethical Supervisor of Constitutional Judges is an effort to uphold the integrity and professionalism of constitutional judges. This research highlights the importance of having an ethical supervisor to maintain the integrity of constitutional judges. The Honor Council of the Constitutional Court plays a central role in carrying out the task of overseeing the behavior and ethics of constitutional judges. The study also analyzes the constitutional foundations and legislation that form the basis for the establishment of the honor council. The research findings demonstrate that the establishment of the Honor Council of the Constitutional Court as the Ethical Supervisor of Constitutional Judges is a significant and relevant step in safeguarding the independence and public trust in the Constitutional Court. Through effective ethical supervision, the honor council can ensure that constitutional judges adhere to high ethical standards in carrying out their duties and responsibilities. This research contributes to the field of constitutional law and judicial ethics by identifying the legal basis and theoretical foundations for the establishment of the honor council as an ethical supervisor. The findings of this research are expected to serve as a reference for further developments concerning regulations and mechanisms for monitoring the ethical conduct of constitutional judges in the future.